Analytical Network Process para avaliação de projetos: um estudo de caso com aplicação da projeção de indicadores contábeis e Value Stream Mapping - Silveira, Antônio Marcos (Universidade do Vale do Rio dos Sinos, 2024)
The competitiveness of the Brazilian industry in the international market has been decreasing over the decade from 2012 to 2022. Due to the challenges faced in this scenario, entrepreneurs in the Brazilian metalworking industry have been looking for investment alternatives in order to improve their products and production processes. However, such plans compete for limited business resources, whose investments are traditionally analyzed by the methods of analysis of Net Present Value (NPV), Internal Rate of Return (IRR) and Discounted Payback (PBD), which do not contemplate a more objective look at the impacts of investments on organizational economic and financial results. The present study aimed at evaluating whether the prioritization of process improvement projects is changed by adopting as a fundamental criterion the impact of these projects on organizational economic and financial results. By means of applied research, with a quantitative approach, open unstructured interviews were conducted with the management and project team of a metalworking industry located in the northwest region of the state of Rio Grande do Sul, evaluating the data of its projects and its financial results. It was found that there was a change in the prioritization of the company's process improvement projects when adopting the proposed ANP model compared to the traditionally adopted investment analysis models. While Project D was chosen when considered the highest NPV (R$ 40,632) and Project B from the perspective of the highest IRR (22.71%) and the lowest Discounted Payback (2.38), Project D obtained the highest rate of prioritization of choice in the proposed ANP model (0.33), even though having had a negative NPV (R$ -321,387), lower IRR (1.26%), higher Discounted Payback (3.98) and negative ROI (-13.15%). It was evidenced that the NPV and IRR are incapable of providing a holistic view of the effectiveness of organizational investment activities, and may possibly mislead managers, while the ANP model was presented as potentially effective for achieving greater assertiveness in the alignment between the company's economic and financial objectives and decision-making for prioritizing investment projects for process improvement.
Keywords: Value Stream Mapping; Avaliação de investimento; Métodos tradicionais; Modelo ANP; Investment valuation; Traditional methods; Financial statements; ANP Model; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis